(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2023)
This study investigated the method of Shape Grammar to develop a computational technique to generate spatial configuration at the early stage of the design process. In synthesizing the spatial configuration and its variants, the user (i.e., architect) can use this tool as a heuristic way to select and choose a spatial configuration of geometric shapes to represent functional requirements and their relationships. The aim of this study is to propose a new technique for spatial configuration based on parametric rules of a specific style of an architect. Our research methodology is explorative and experimental based on the Shape Grammar theory and analysis of the existing models of architects’ works as a case study. We studied the example of Adolf Loos’s residential works as our basis for the parametric shape rules and the tool developed in the form of a modular cluster component in the Visual Programming Language Grasshopper in a Rhinoceros 3D modeling software. This cluster component, termed "Rupa," is parametrically modeled and consists of two main algorithms: 1) two-dimensional and three-dimensional rules-based shape generation and 2) the transformation rules of translation, rotation, reflection, dilatation, and tension. Using this component, the user can create and transform a shape configuration by its parameters, constrained only by the characteristics of Adolf Loos’s residential works design rules as the underlying principles behind the component. Although limited only to three of Loos’s residential works, this experiment has successfully generated residential spatial configuration designs based on the constraint rules of Adolf Loos’s residential works. The result shows the potential of this technique and tool in aiding architects to create design variants and select those that are the most optimal.